Immunohistochemical expression of endocan, as a marker of assessment of angiogenic potential in benign vascular lesions (hemangioma, lymphangioma and lobular capillary hemangioma) of head and neck region - Tater, Jawaher M; Abdullah, Bashar H; Hussain, Wisam A (Journal of Baghdad College of Dentistry, 2018)
BACKGROUND: Vascular tumors are a heterogeneous group of diseases with biological behavior ranging from a hamartomatous growth to frank malignant. The pathophysiology of lymphangioma, vascular malformation and hemangioma is interconnected, blood vessels known to be the site of origin of hamartomas, venous malformations and some neoplasms as benign, tumor-like growth of vessels (hemangiomas). Angiogenesis is the process of formation of new blood vessels from an existing structure. Aims of study Assessment of angiogenic potential in benign vascular lesions (hemangioma, lymphangioma and lobular capillary hemangioma) of head and neck region. Materials and Methods: Twenty-two formalin-fixed paraffin-embedded tissue blocks of Hemangioma/vascular malformation, thirty of lobular capillary hemangioma and another twenty of lymphangioma to be stained with Endothelial cell-Specific Molecule-1 (ESM-1) monoclonal antibody. Results: Microvessel density expressed by Endothelial cell-Specific Molecule-1 (ESM-1) immunomarker was found in all cases with mean density of (37.44±23.16) for lobular capillary hemangioma and (25.02±13.89) for hemangioma and (6.34±3.52) for lymphangioma. According to post hoc test ESM-1 marker expression showed a high significant difference between (hemangioma and lymphangioma=0.001), (lymphangioma, pyogenic granuloma=0.000), and it was significantly different between (hemangioma, pyogenic granuloma=0.011) Conclusions: The obvious capillary growth in lobular capillary hemangioma revealed that lobular capillary hemangioma showed the highest activity of angiogenic potential in comparison to hemangioma and lymphangioma.